| //@ run-pass |
| #![allow(dead_code)] |
| |
| enum Enum { |
| Foo { foo: usize }, |
| Bar { bar: usize } |
| } |
| |
| fn fun1(e1: &Enum, e2: &Enum) -> usize { |
| match (e1, e2) { |
| (&Enum::Foo { foo: _ }, &Enum::Foo { foo: _ }) => 0, |
| (&Enum::Foo { foo: _ }, &Enum::Bar { bar: _ }) => 1, |
| (&Enum::Bar { bar: _ }, &Enum::Bar { bar: _ }) => 2, |
| (&Enum::Bar { bar: _ }, &Enum::Foo { foo: _ }) => 3, |
| } |
| } |
| |
| fn fun2(e1: &Enum, e2: &Enum) -> usize { |
| match (e1, e2) { |
| (&Enum::Foo { foo: _ }, &Enum::Foo { foo: _ }) => 0, |
| (&Enum::Foo { foo: _ }, _ ) => 1, |
| (&Enum::Bar { bar: _ }, &Enum::Bar { bar: _ }) => 2, |
| (&Enum::Bar { bar: _ }, _ ) => 3, |
| } |
| } |
| |
| pub fn main() { |
| let foo = Enum::Foo { foo: 1 }; |
| let bar = Enum::Bar { bar: 1 }; |
| |
| assert_eq!(fun1(&foo, &foo), 0); |
| assert_eq!(fun1(&foo, &bar), 1); |
| assert_eq!(fun1(&bar, &bar), 2); |
| assert_eq!(fun1(&bar, &foo), 3); |
| |
| assert_eq!(fun2(&foo, &foo), 0); |
| assert_eq!(fun2(&foo, &bar), 1); // fun2 returns 0 |
| assert_eq!(fun2(&bar, &bar), 2); |
| assert_eq!(fun2(&bar, &foo), 3); // fun2 returns 2 |
| } |